Annual Report and Accounts for the year ended 30th June, 1979 (The Southern African Institute of Mining and Metallurgy, 1979)
Council and Standing Committees, 1978-1979 President: Dr M. G. Atmore. Vice-Presidents: D. A. Viljoen and Dr P. R. Jochens. Honorary Treasurer: J. K. E. Douglas. Immediate Past President: P. A. von Wielligh. Members of Council: J. D. Austin, A. N. Brown, H. E. James, Prof. R. P. King, Dr D. G. Krige, Prof. F. Q. P. Leiding, D. G. Malan, C. S. McPhail, J. C. Mostert, G. Y. Nisbet, H. G. M. Rose, W. T. Ruhmer, G. C. Thompson, R. A. von Maltitz. Chairman, Witbank-Middelburg Branch: T. S. Wilmot. Chairman, Orange Free State-Klerksdorp Branch: H. M. W. Eschenburg. Past Presidents Serving on Council: R. J. Adamson, H. Britten, J. K. E. Douglas, Prof. D. D. Howat, Dr J. P. Hugo, D. G. Maxwell, Prof. R. P. Plewman, Dr R. E. Robinson, Dr M. D. G. Salamon, P. W. J. van Rensburg. Standing Committee Chairmen: Membership, Dr P. R. Jochens ; Technical Programme - Metallurgy, Prof. R. P. King ; Technical Programme - Mining, H. G. M. Rose; Vacation School - Metallurgy, J. C. Mostert; Vacation School - Mining, D. G. Malan/J. D. Austin; Awards, P. A. von Wielligh; Excursions, D. A. Viljoen; Adjudication, P. A. von Wielligh; Constitution, Rules and Policy, P. A. von Wielligh; Monograph Series, Dr R. E. Robinson; Professional and Technician Train¬ing Committee, Dr M. D. G. Salamon; Career Guidance, D. G. Malan; Phoenix National Committee, Dr R. E. Robinson; 1982 World Congress, Dr M. G. Atmore; Witbank Coal Colloquium, Dr P. R. Jochens; Mines and Works, P. A. von Wielligh.